HASIL PEMERIKSAAN KOLESTEROL TOTAL PADA SERUM SEGERA DIPERIKSA DAN DITUNDA 7 HARI PADA SUHU 2 - 8ºC: RESULTS OF TOTAL CHOLESTEROL EXAMINATION IN THE IMMEDIATE SERUM CHECKED AND DELAYED 7 DAYS AT TEMPERATURE 2-8ºC - Alfina Amelda; Asrori Asrori; Karneli Karneli (Klinikal Sains : Jurnal Analis Kesehatan, 2020)
Background: Lipid profile examination that is often done in a laboratory is an examination of total cholesterol, which can be done by using a serum specimen. Although it is highly recommended to do a direct serum check, there are a number of reasons for delaying the examination, such as a broken device, or a power outage that makes the examination must be postponed. Serum that is not immediately checked can be stored. Storage of specimens is one of the pre-analytic stages, which has a significant risk of error in a laboratory examination. Objectives: This study aims to determine the comparison of the results of total cholesterol in serum which is immediately checked and postponed for 7 days at a temperature of 2-8ºC. Methods: This research was an experimental study with one group pre and posttest design. The population of this study were all Level 1 and 2 Students of Health Analyst Department of Health Ministry of Health, Palembang in 2020, totaling 150 people. The sample of this study was serum from 30 respondents taken by simple random sampling. Total cholesterol levels were checked using the Biosystem bts-350. Results: From the Shapiro Wilk data normality test obtained data with normal distribution. Data analysis continued with t dependent test, p = 0.403 was obtained, it means that p> α (0.05), which means there was no difference in the results of the examination of total cholesterol levels in serum that was immediately examined and stored for 7 days at a temperature of 2-8ºC. Conclusion: It can be concluded that there is no significant difference in the results of the examination of total cholesterol levels in serum that are immediately examined and stored for 7 days at a temperature of 2-8ºC.